Cadena logística de exportación de banano del Ecuador - Coello Salguero, Maria (2009)
Ecuador is the leading exporter of bananas. This activity generates currencies and employment for all the people who are directly and indirectly involved to this activity. This paper aims to raise awareness of the characteristics and the importance of the logistics chain for the exportation of bananas from their farms to the final consumer since there are some difficulties that prevent the efficient development of its various processes, this analysis will consist of variables directly related to the exportation of bananas, analyzing not only the banana market, reflecting both the offer and demand status but the evolution of prices per box comparing both the price that is paid to the producer and the minimal official one. The evolution of Ecuadorian exportations identifying the destination countries will also be analyzed. Inside the regulatory framework the non-tariff and tariff regulations will be discussed. The identification of the productivity and rating zones, internal and transportation costs and international current status of the road network banana will be analyzed afterwards.